Institutionalized Interdisciplinary Approaches in Architectural and Design Education (Prostor, 2024)
This paper investigates the multifaceted realm of interdisciplinarity in architectural education, examining historical and contemporary perspectives from institutions such as the Bauhaus, the Ulm School of Design, TU Delft, and the University of Zagreb Faculty of Architecture. Acknowledging the challenges posed by complex urban issues, the study underscores the imperative for interdisciplinary approaches in addressing economic, social, and ecological crises. By tracing the evolution of the concept, the paper distinguishes between disciplinary and interdisciplinary approaches, exploring key definitions of the concept. The paper concludes by highlighting ongoing efforts in educational institutions, reflected in various courses, workshops, and summer schools. Despite the limitations inherent in examining a handful of examples, the findings offer valuable guidance for educational institutions aspiring to embrace or enhance interdisciplinary approaches in architectural education. The insights draw attention to the importance of holistic, collaborative models in preparing future architects to navigate the complexities of our urban environments.